Koreografi Tari Indang Randai Di Sanggar Alang Bangkeh Silaing Bawah Kota Padang Panjang - Uthi Sonia; Herlinda Mansyur (FBS Universitas Negeri Padang, 2020)
This study aims to reveal and describe the choreography form of Indang Randai Dance at Alang Bangkeh Studio, Silaing Bawah, Padang Panjang city. This is a qualitative research using descriptive method. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing instruments and cameras. The data used were primary and secondary data. The data were collected through interview, observation, and documentation. The data analysis was conducted by collecting the data, reducing the data, presenting the data, and making conclusions. The results show that Indang Randai dance is a creative dance whichholds the characteristics of Minangkabau women and rules which exist in Minangkabau custom. This dance tells about the joy of teenagers in doing activities. The dance functions as an entertainment dance. Related to the dance elements, Indang Randai dance choreography consists of 59 dance movements, the upper design dominantly using low design, the floor design which is dominantly from straight line developments, the music design, and the dramatic group choreography design. The dynamics are generally intermediate. The group choreography is performed simultaneously and balanced. The costumes worn are galembong pants, bajukurung, tokah, waist bands, and accessories. The dancers use stage make-up. From all those dance elements, relation to the theme of the daily activities of teenagers who are happy and enthusiastic in carrying out activities can be made.